Tremont Street, ca. 1885 - Unknown (Tufts Archival Research Center, 2005)
Elevated view northeast of Tremont Street. Signage and awnings adorn the facades of buildings lining the east-southeast side of Tremont Street, which are visible along the right side of the photograph. The Granary Burying Ground is included along the left side of the photograph. The facade and south-southwest elevation of Tremont House, located at the southwest corner of Tremont and Beacon Streets, line the northeast side of the Granary Burying Ground. Horse-drawn wagons and horse railroads line Tremont Street, and pedestrians fill the sidewalks. 7 11/16 x 9 5/16, 7 7/8 x 9 9/16 overall Photographs